Effect of sequencing strength and endurance training in young male soccer players - Makhlouf, I.; Castagna, C.; Manzi, V.; Laurencelle, L.; Behm, D. G.; Chaouachi, A. (The Journal of Strength and Conditioning Research, 2016)
This study examined the effects of strength and endurance training sequence (strength before or after endurance) on relevant fitness variables in youth soccer players. Fifty-seven young elite-level male field soccer players (13.7 ± 0.5 years; 164 ± 8.3 cm; 53.5 ± 8.6 kg; body fat; 15.6 ± 3.9%) were randomly assigned to a control (n = 14, CG) and 3 experimental training groups (twice a week for 12 weeks) strength before (SE, n = 15), after (ES, n = 14) or on alternate days (ASE, n = 14) with endurance training. A significant (p = 0.001) intervention main effect was detected. There were only trivial training sequence differences (ES vs. SE) for all variables (p > 0.05). The CG showed large squat 1 repetition maximum (1RM) and medium sprint, change of direction ability, and jump improvements. ASE demonstrated a trivial difference in endurance performance with ES and SE (p > 0.05). Large to medium greater improvements for SE and ES were reported compared with ASE for sprinting over 10 and 30 m (p < 0.02). The SE squat 1RM was higher than in ASE (moderate, p < 0.02). Postintervention differences between ES and SE with CG fitness variables were small to medium (p = 0.05) except for a large SE advantage with the Yo-Yo intermittent recovery test (p < 0.001, large). This study showed no effect of intrasession training sequence on soccer fitness-relevant variables. However, combining strength and endurance within a single training session provided superior results vs. training on alternate days. Concurrent training may be considered as an effective and safe training method for the development of the prospective soccer player.